(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Zinc supplementation is a critical new intervention for treating diarrheal episodes in children. Recent studies suggest that administration of zinc along with new low osmolarity oral rehydration solutions / salts (ORS) can reduce the duration and severity of diarrheal episodes for up to three months. Several mechanisms of action of zinc has been proposed, however there is dearth of information about the effect of zinc on intestinal motility during diarrhea. Male albino Wistar rats (80-100g) were used. The effect of different doses of zinc sulphate (25, 50, 100, 150mg/Kg) on the number of wet faeces was investigated. Intestinal motility during castor oil induced diarrhea was assessed using activated charcoal meal and the mechanisms of action of zinc sulphate on motility were investigated. The effective dose of zinc sulphate (100mg/Kg) significantly reduced (p< 0.001) the number of wet faeces (3.0 ± 0.00) compared with control (6.8 ± 0.25) during diarrhea. This antidiarrheal effect of zinc was abolished by propranolol and nifedipine. Zinc sulphate significantly reduced (p< 0.05) intestinal transit time (60.7 ± 7.13%) compared with control (85.7 ± 2.35%). It is concluded that zinc sulphate reduces the frequency of wet faeces output and intestinal motility during diarrhea via activation of β adrenergic receptor and L-type Ca2+ channel.